Potassium usnate, a water-soluble usnic acid salt, shows enhanced bioavailability and inhibits invasion and metastasis in colorectal cancer. Issue 1 (December 2018) - Yang, Yi; Bae, Woo; Lee, Ji-Yoon; Choi, Yong; Lee, Kyung; Park, Myong-Suk; Yu, Young; Park, So-Yeon; Zhou, Rui; Taş, İsa and Gamage, Chathurika and Paik, Man-Jeong and Lee, Jae and Chung, Ik and Kim, Kyung and Hur, Jae-Seoun and Kim, Sang and Ha, Hyung-Ho and Kim, Hangun
Abstract Usnic acid (UA), a lichen secondary substance, has considerable anticancer activityin vitro, whereas its effectin vivo is limited. Here, potassium usnate (KU) was prepared by the salinization of UA to enhance its water solubility. KU showed increased bioavailability compared with UA in the tumor, liver, and plasma of a CT26 syngeneic mouse tumor xenograft model after oral administration, as determined by LC-MS/MS analysis. KU exhibited potent anticancer effects on colorectal cancer cells and inhibited liver metastasis in an orthotopic murine colorectal cancer model. KU treatment downregulated the epithelial-mesenchymal markers Twist, Snail, and Slug and the metastasis-related genesCAPN1, CDC42, CFL1, IGF1, WASF1, andWASL in cells and tumor tissues. The present results suggest the potential application of the water-soluble form of UA, KU, in anticancer therapy.